Numerical Analysis of the Influence of Foundation Replacement Materials on the Hydrothermal Variation and Deformation Process of Highway Subgrades in Permafrost Regions - Wei Shan; Min Ma; Ying Guo; Chengcheng Zhang (Water, 2022)
Affected by global warming, permafrost thawing in Northeast China promotes issues including highway subgrade instability and settlement. The traditional design concept based on protecting permafrost is unsuitable for regional highway construction. Based on the design concept of allowing permafrost thawing and the thermodynamic characteristics of a block–stone layer structure, a new subgrade structure using a large block–stone layer to replace the permafrost layer in a foundation is proposed and has successfully been practiced in the Walagan–Xilinji section of the Beijing–Mohe Highway to reduce subgrade settlement. To compare and study the improvement in the new structure on the subgrade stability, a coupling model of liquid water, vapor, heat and deformation is proposed to simulate the hydrothermal variation and deformation mechanism of different structures within 20 years of highway completion. The results show that the proposed block–stone structure can effectively reduce the permafrost degradation rate and liquid water content in the active layer to improve subgrade deformation. During the freezing period, when the water in the active layer under the subgrade slope and natural ground surface refreezes, two types of freezing forms, scattered ice crystals and continuous ice lenses, will form, which have different retardation coefficients for hydrothermal migration. These forms are discussed separately, and the subgrade deformation is corrected. From 2019 to 2039, the maximum cumulative settlement and the maximum transverse deformation of the replacement block–stone, breccia and gravel subgrades are –0.211 cm and +0.111 cm, –23.467 cm and –1.209 cm, and –33.793 cm and –2.207 cm, respectively. The replacement block–stone subgrade structure can not only reduce the cumulative settlement and frost heave but also reduce the transverse deformation and longitudinal cracks to effectively improve subgrade stability. However, both the vertical deformation and transverse deformation of the other two subgrades are too ...